Non-alcoholic Fatty Liver Disease (NAFLD) is associated with impairment of Health Related Quality of Life (HRQOL). Issue 1 (December 2016) - Golabi, Pegah; Otgonsuren, Munkhzul; Cable, Rebecca; Felix, Sean; Koenig, Aaron; Sayiner, Mehmet; Younossi, Zobair
Abstract Background NAFLD impacts patient reported outcomes (PROs). Our aim was to assess the impact of NAFLD on patients' HRQOL. Methods National Health and Nutrition Examination Survey (NHANES) 2001–2011 data were used to identify adult patients with NAFLD [Fatty Liver Index (FLI) > 60 in absence of other liver disease and excessive alcohol >20 g/day for men, >10 g/day for women]. Patients with other chronic diseases (ex. HIV, cancer, end-stage kidney disease) were excluded. Subjects without any of these conditions were healthy controls. HCV RNA (+) patients were HCV-controls. All patients completed NHANES HRQOL-4 questionnaire. Linear regression determined the association between NAFLD and HRQOL components adjusting for age, gender, race, and BMI. Results Participants with complete data were included (n = 9661); 3333 NAFLD (age 51 years and BMI 34 kg/m2 ); 346 HCV+ (age 49 years; BMI 27 kg/m2 ) and 5982 healthy controls (age 48 years and BMI 26 kg/m2 ). The proportion of subjects rating their health as "fair" or "poor" in descending order were HCV controls (30 %) NAFLD (20 %) and healthy controls (10 %) (p < 0.001). HRQOL-4 components scores 2–4 were lowest for HCV, followed by NAFLD and then healthy controls (p-valuesp = 0.011 to < .0001). After adjustment for age, gender, race, and BMI, NAFLD patients were 18–20 % more likely to report days when their physical health wasn't good or were unable to perform daily activities as a result (p < .0001). Conclusions NAFLD causes impairment of HRQOL. As NAFLD is becoming the most important cause of CLD, its clinical and PRO impact must be assessed.